The Problems Experienced by Parents Providing Postoperative Home Care Following Their Child's Surgery for Developmental Dysplasia of the Hip. (September 2015) - Demir, Sevil Guler; Erden, Sevilay; Bulut, Hulya; Carboga, Banu; Elbas, Nalan Ozhan
<x xml:space="preserve">Abstract</x> BACKGROUND: Families, especially mothers, experience problems providing home care after their child's surgery for developmental dysplasia of the hip (DDH). PURPOSE: To assess the problems experienced by parents providing postoperative home care to their child after DDH surgery. METHODS: This was a descriptive cross-sectional study. The sample consisted of 33 parents. Data were collected through a survey conducted at the hospital following the child's surgery and by telephone 4–6 weeks after surgery. Frequencies, means, percentages, and chi-square tests were used to analyze the data. RESULTS: The parents (93.9% women) provided postoperative care for approximately 3 months. Nearly all of the parents (97%) had physical (96.9%), psychological (65.6%), and social (75.0%) problems in addition to child care problems. CONCLUSIONS: We recommend preparing a comprehensive discharge-training package for parents after their child's DDH surgery, supplementing home care instructions with visual training materials, and providing telephone counseling to parents after discharge.